Predictors of Ventilator Weaning Failure in Sepsis Patients in Intensive Care Unit - Dwisusanti, Oktina; Rohman, Rohman; Yunitri, Ninik; Rayasari, Fitriyan; Anitha, Anitha; Maemun, Siti (GLOBAL HEALTH SCIENCE GROUP, 2024)
Sepsis is one of the most common infection complications in intensive care units (ICU). Sepsis causes organ dysfunction, including respiratory failure, that requires ventilator breath support. However, patients often experience ventilator weaning failure. We analyse the relation of predictor ventilator weaning failure in sepsis patients in ICU. This study was a cross-sectional study with study population consisting of sepsis patients who used ventilators in the ICU of Sulianti Saroso Hospital, and there were as many as 58 patients. We studied age, gender, body mass index (BMI), PCO2 value, prolonged ventilator use, pneumonia, malnutrition, vasopressor use and ventilator weaning with secondary data. The data collection instruments used were case report formulas. Descriptive statistical analysis in the form of frequency distribution (n) and proportion (%) and further analysis with binomial logistic regression (α<0.05). Three factors significantly influenced weaning failure were vasopressor use, malnutrition, and BMI (p<0.05). There is a significant influence of vasopressor use, malnutrition, and BMI with ventilator weaning failure.